Harmonisasi Antara Islam dan Kristen Di Tana Toraja - Kamaruddin Mustamin; Sunandar Macpal; Yunus Yunus (Institut Agama Islam Negeri Kendari, 2022)
Abstract This study aims to describe the harmonization of Muslims and Christians in Tana Toraja. Philosophically it can be described as a representation of local wisdom and awareness. This study uses a qualitative method. Researchers hear, record, and understand the condition of the community as a whole about the values and meaning of the Toraja people's outlook on life. In Toraja society, in one family and even in one house you can find adherents of different religions, but they remain harmonious and peaceful thanks to the customs and philosophy of local wisdom of Tongkonan. Culture in society cannot be measured using data in the form of numbers, because researchers use qualitative methods. Based on the results of the research it is known that one form of harmonization is the creation of a community in society which is a very important social fact in a pluralistic society. In dealing with pluralism, the Toraja people are able to be tolerant of pluralism and are required to live in a pluralist spirit. This can be applied in interfaith life where religious differences do not have to be an obstacle in establishing brotherhood, unity and national unity. Keywords: Harmonization, Local Wisdom, Toraja